Action-Shapers and Their Neuro-Immunological Foundations - Paans, Otto; Ehlen, Boukje (Frontiers in Psychology, 2022)
Not all our intentions translate into actions, as our capacity to act may be influenced by a variety of mental and biochemical factors. In this article, we present a comprehensive account of how neuro-immunological processes affect our intentional abilities and our capacity to act. We do so by extending the theory of thought-shapers (TTS) through the notion of action-shapers and combining this theory with the essential embodiment thesis (EE). This thesis about the mind-body relation says that human minds are necessarily and completely embodied. Action-shapers dynamically constitute the action-space of individuals, affecting their capacity to take action or to select one course of action over another. We highlight the effects and interactions of neuro-immunological effective processes in the body to demonstrate how they shape the action-space. In this article, we consider neuro-immunological effective processes that influence the gut-brain axis, chronic stress, high levels of sugar intake, the amygdala and the effects of prolonged stress. We investigate the effects of these processes on the perception and on the capacity to form intentions and act on them. We conclude the paper by providing a concise account of action-shapers, in which we attempt to summarize the line of argumentation and provide suggestions for further research.